Potensi Kentos Kelapa (Cocos nucifera) Sebagai Media Pertumbuhan Efektif Jamur Candida albicans - Bastian Bastian; Denny Juraijin; Cut Nur’azimah Putri Rico (FORIKES, 2024)
Candida albicans fungus requires a source of nutrients, especially carbohydrates, to grow and reproduce. Identification of isolation and confirmation of microscopic examination results require culture media. Coconut kentos (Cocos nucifera) has 66% carbohydrates, vitamins, and other nutrients. This study aimed to analyze the differences in the number of colonies and diameter of Candida albicans fungus on Sabouraud Dextrose Agar media, alternative coconut kentos media (Cocos nucifera) in various concentrations of 100%, 75%, 50%, and 25%. The design of this study was a posttest only with control design, which was conducted in a microbiology laboratory, involving 30 samples. The samples were divided into 6 groups, namely Sabouraud Dextrose Agar media), coconut kentos with concentrations of 100%, 75%, 50%, and 25%. Furthermore, measurements of fungal colonies and fungal diameter were carried out by observation. The results showed that the average value of fungal colonies and the diameter of Candida albicans fungal colonies with optimum concentrations of 50% (71.75 CFU/mL) and 75% (0.70 mm) because at these concentrations the number of diameters and the number of colonies approached the standard media (SDA media) (69.5 CFU/mL) and a colony diameter of 0.50 mm and the ANOVA test obtained a p value = <0.000, which means there was a difference in fungal colonies and diameters between groups. Based on the results of the analysis, it was concluded that coconut kentos can be used as an alternative medium for the growth of Candida albicans fungiKeywords: Candida albicans; coconut kentos; Sabouraud Dextrose Agar ABSTRAK Jamur Candida albicans membutuhkan sumber nutrisi terutama karbohidrat untuk tumbuh dan berkembang biak. Identifikasi isolasi dan konfirmasi hasil pemeriksaan secara mikroskopis memerlukan media kultur. Kentos kelapa (Cocos nucifera) mempunyai karbohidrat sebanyak 66% vitamin, dan nutrisi lainnya. Penelitian ini bertujuan untuk menganalisis perbedaan jumlah koloni dan diameter jamur Candida albicans pada media Sabouraud Dextrosa Agar, media alternatif kentos kelapa (Cocos nucifera) dalam berbagai konsentrasi 100%, 75%, 50%, dan 25%. Rancangan penelitian ini adalah posttest only with control design, yang dilakukan di laboratorium mikrobiologi, yang melibatkan 30 sampel. Sampel dibagi menjadi 6 kelompok yakni media Sabouraud Dextrosa Agar), kentos kelapa dengan konsentrasi 100%, 75%, 50%, dan 25%. Selanjutnya dilakukan pengukuran koloni jamur dan diameter jamur dengan cara observasi. Hasil penelitian menunjukkan bahwa nilai rata-rata koloni jamur dan diameter koloni jamur Candida albicans dengan konsentrasi optimum yaitu 50% (71,75 CFU/mL) dan 75% (0,70 mm) dikarenakan pada kosentarsi tersebut jumlah diameter dan jumlah koloninya mendekati media standard (media SDA) (69,5 CFU/mL) dan diameter koloni 0,50 mm serta dilakukan uji ANOVA didapatkan nilai p = < 0,000, yang berarti ada perbedaan koloni dan diameter jamur antara kelompok. Berdasarkan hasil analisis disimpulkan bahwa kentos kelapa dapat digunakan sebagai media alternatif pertumbuhan jamur Candida albicans.Kata kunci: Candida albicans; kentos kelapa; Sabouraud Dextrosa Agar